Amoebal endosymbiont Neochlamydia genome sequence illuminates the bacterial role in the defense of the host amoebae against Legionella pneumophila. - Kasumi Ishida (Public Library of Science (PLoS), 2014)
Previous work has shown that the obligate intracellular amoebal endosymbiont Neochlamydia S13, an environmental chlamydia strain, has an amoebal infection rate of 100%, but does not cause amoebal lysis and lacks transferability to other host amoebae. The underlying mechanism for these observations remains unknown. In this study, we found that the host amoeba could completely evade Legionella infection. The draft genome sequence of Neochlamydia S13 revealed several defects in essential metabolic pathways, as well as unique molecules with leucine-rich repeats (LRRs) and ankyrin domains, responsible for protein-protein interaction. Neochlamydia S13 lacked an intact tricarboxylic acid cycle and had an incomplete respiratory chain. ADP/ATP translocases, ATP-binding cassette transporters, and secretion systems (types II and III) were well conserved, but no type IV secretion system was found. The number of outer membrane proteins (OmcB, PomS, 76-kDa protein, and OmpW) was limited. Interestingly, genes predicting unique proteins with LRRs (30 genes) or ankyrin domains (one gene) were identified. Furthermore, 33 transposases were found, possibly explaining the drastic genome modification. Taken together, the genomic features of Neochlamydia S13 explain the intimate interaction with the host amoeba to compensate for bacterial metabolic defects, and illuminate the role of the endosymbiont in the defense of the host amoebae against Legionella infection.